(untitled) (Public Sector Economics - submission site, 2023)
This research focuses on the prediction of the probability of (re)entering high financial stress (via a large set of cyclical risk accumulation indicators). The focus is placed on a specific single-country analysis to obtain answers to questions about which indicators are best in explaining the future probability of (re)entering a high-stress regime. This allows the policymaker to get a better focus on the best-performing variables. It is challenging to monitor a whole set of indicators of cyclical risk build-up; the results could bring into focus a smaller group of the essential variables. The contribution of this paper is in finding a set of indicators that help in forecasting financial stress, in terms of switching from one regime to another. The regime-switching models’ results indicate that some credit specifications, house price dynamics, and debt burden could be best monitored for the case of Croatian data.